Comparison of the Relationships between Traditional and Regional Bone Mineral Density Values and Strength and Lean Mass for Younger and Older Women - Michele LeBlanc; Tracy White; Steve Hawkins (Journal of Mid-Life Health)
Background: While studies focused on the relationships between bone mineral density (BMD) and strength or lean body mass have been conducted, there are not studies that have investigated these relationships for both age groups using the same methodology and population criteria (especially physical activity levels). Aims and Objectives: The aim of this study was to compare the relationships between traditional and regional bone mineral density (BMD) and strength and lean mass values in younger and older women. Materials and Methods: Forty-four younger (18–30 years) and 40 older (65–80 years) healthy females were recruited for this study. All had a physical activity rating of four or lower on the Physical Activity Rating Questionnaire. Muscle strength was tested for hand grip, leg press, and isokinetic knee flexion and extension. Total and regional lean body mass and BMD values were determined using dual-energy x-ray absorptiometry (DXA). Correlations and stepwise regressions were run between traditional (hip, spine, and forearm) and regional (arm and leg) BMD and strength and lean mass values. Significance was determined with P < 0.05. Results: The relationships for traditional BMD and strength measures for the two groups were quite similar with few significant relationships being identified for either group. The two groups had differing relationships between traditional BMD values and lean mass measures. The relationships between regional BMD and strength and lean mass values had good agreement for the two groups for the arm, but not the leg. Conclusions: The relationships investigated were most similar between the two age groups for the upper body but did not have good agreement for the lower body. These differences were likely due to greater declines in muscle quality associated with aging that occur more drastically for the lower body.